2013
DOI: 10.1111/head.12129
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Interictal Vestibular Function in Vestibular Migraine vs Migraine Without Vertigo

Abstract: Vestibular abnormalities were present interictally among both VM and M patients, but were found about twice as frequently among VM patients. This may indicate that subclinical vestibular dysfunction is an integral part of migraine pathology in general, and not solely in VM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 35 publications
5
54
1
7
Order By: Relevance
“…In general, the caloric peak slow-phase velocity values tend to be elevated in VM patients compared to MD [65,66]. Remember, there is also a portion of common migraine patients which have a UW in between the attacks (16%) [67].…”
Section: Vestibular Migraine (Vm)mentioning
confidence: 99%
“…In general, the caloric peak slow-phase velocity values tend to be elevated in VM patients compared to MD [65,66]. Remember, there is also a portion of common migraine patients which have a UW in between the attacks (16%) [67].…”
Section: Vestibular Migraine (Vm)mentioning
confidence: 99%
“…In attack-free periods, spontaneous nystagmus is rare. Positional nystagmus of central origin occurs in 10–20% of patients [52, 56] and gaze-evoked nystagmus may be rarer [18, 52, 59]. However, a follow-up study by Radtke et al has revealed oculomotor abnormalities between attacks in patients with VM of 16% initially up to 41% after 9 years [52], as corroborated by several other studies [26, 54].…”
Section: Migraine Clinical Manifestationsmentioning
confidence: 72%
“…In 2001, Neuhauser et al proposed the diagnostic criteria for Migrainous Vertigo, which have been widely used since then [17, 18]. More recently (2013), a working group (Bárány Society and International Headache Society) [3] established an expert consensus on the diagnostic criteria currently in use, which are included in an appendix of the third edition of the International Classification of Headache Disorders.…”
Section: Historical Perspectivementioning
confidence: 99%
See 2 more Smart Citations